A study on perinatal outcomes in antenatal mothers with abnormal pulmonary function tests - Sengodan, Subha Sivagami; Palanivelu, Anandeswari; Pandian, Anbarasi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was done to assess the lung volumes by spirometry in all the three trimesters in antenatal mothers and to observe the effect of pulmonary function abnormality in mode of delivery and birth weight of babies. Methods: Our study included 100 antenatal mothers attending antenatal clinic in Government Mohan Kumaramangalam Medical College, Salem, Tamil Nadu during the period of Jan 2017 to Dec 2017. It was a prospective observational study. Mothers were subjected to detailed physical and clinical examination. Basic investigations were done. Considering test by spirometry. The changes in the lung volumes were noted according to gestational age. The effect of pulmonary function abnormality in the mode of delivery and birth weight was observed. Results: One hundred antenatal mothers selected randomly were evaluated for the lung volumes by using spirometry. Out of the 100 cases, 17 belonged to I trimester, 46 belonged to II trimester and 37 belonged to III trimester. We noted a significant reduction in FVC in II and III trimester. This reduction was little more in II trimester. There was significant reduction in FEV1 in II trimester. The reduction in FEV1 and FVC did not influence the mode of delivery but it significantly affected the birth weight of babies. FEV1/FVC reduction had no influence in the mode of delivery and birth weight of babies. Conclusions: The present study highlighted that there was reduction in lung volumes in II and III trimester of pregnancy and it influenced the birth weight of babies. Hence it becomes essential to pay special attention to pulmonary functions during antenatal period.